How traditional healers diagnose and treat diabetes mellitus in the Pretoria Mamelodi area and how do these purported medications comply with complementary and alternative medicine regulations - Muntingh, George L. (University of Pretoria, 2019)
Dissertation (MSc)--University of Pretoria, 2019.